Experiences of Parents Whose Newborns Undergo Hypothermia Treatment Following Perinatal Asphyxia. Issue 1 (20th November 2012) - Nassef, Sari Kokkonen; Blennow, Mats; Jirwe, Maria
ABSTRACT: Objective: To describe and interpret experiences of parents whose newborns are treated with induced hypothermia following perinatal asphyxia. Design: A qualitative exploratory study. Setting: Data collection in parental home environments ( n = 8) and in a study room in a university library ( n = 2). Participants: A total of 10 parents, seven mothers and three fathers, participated in the study. Their newborns were treated with induced hypothermia 4 to 12 months prior to the interviews. Methods: Recorded open‐ended interviews with the participants lasted from 60 to 90 minutes. Field notes were made after each interview. The interviews were transcribed verbatim and inductive content analysis was used in the analyzing process. Results: Four main themes emerged from the data: emotional landscapes, adaptation to a new situation (with subthemes creating control, external and internal support in a difficult situation, normalizing the abnormal and reconciling oneself to uncertainty), moments of rebirth, and change in attitude toward life and existence. Conclusion: Term newborns are treated with induced hypothermia treatment due to perinatal asphyxia. During the hospitalization of newborns in neonatal intensive care units (NICUs), parents experience high levels of stress. Parents use several strategies for adapting to this situation, and nurses play a pivotal role in providing individual support and acting as advocates for parents in the NICU. After the infants are rewarmed, parents experience a moment of rebirth that might help them attach to their infants. Further research is warranted in this area to provide holistic care and support to families whose neonates undergo this treatment.